Influence of interaction between community health workers and adults with chronic diseases on risk mitigation through care coordination. (June 2022) - Chiyaka, Edward T; Lanese, Bethany; Bruckman, David; Redding, Mark; Filla, Joshua; Ferguson, Pamela; Hoornbeek, John
Introduction: Addressing health disparities and barriers to care requires a comprehensive approach that involves participation of health care providers, multiple organizations, and service providers in the communities affected. Given the importance of using community health workers to help address the complex and overlapping medical, social, and behavioral needs of high-risk individuals, it is of utmost importance to understand their impact on health outcomes. This study examines how in-person interaction between community health workers and their clients influence the client's level of risk mitigation achieved through care coordination using the Pathways Community HUB model. Methods: The study utilized two years of data extracted from the Care Coordination Systems database for 391 adults who participated in the Northwest Ohio Pathways Community HUB program. Using multinomial logistic regression analysis, we assessed how the interaction between community health workers and adults with chronic diseases who participated in the Northwest Ohio Pathways Community HUB program influenced the successful mitigation of their social, behavioral, and other medical risks over a 2-year period. Results: Our findings show that as the number of in-person contacts between the community health worker and the client increased, the likelihood of completing all Pathways increased by 27% when compared to completing less than 50% of the assigned Pathways, after adjusting for potential confounders (odds ratio: 1.27, 95% confidence interval: 1.07−1.52). Discussion: Using community health workers as part of care coordination teams may be effective in connecting communities to systems of care, helping individuals manage their health conditions and connecting individuals to needed social services. Their direct in-person interaction with at-risk individuals may increase the extent to which these individuals successfully address risks to their health and well-being.